Berbagai Lama Penyimpanan Daging Ayam Broiler Segar Dalam Kemasan Plastik Pada Lemari Es (Suhu 4oC) Dan Pengaruhnya Terhadap Sifat Fisik Dan Organoleptik - Achmad Jaelani; Siti Dharmawati; Wanda Wanda (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2014)
The purpose of this study was to determine the extent of the influence of storage time fresh broiler chicken meat on plastic packaged in the refrigerator (4oC) to pH, water holding capacity and cooking loss and organoleptic (flavor, texture and color). The research was used Completely Randomized Design (CRD) with 5 treatments, namely: (P0) = storage for 0 day; (P6) = storage for 6 days; (P12) = storage for 12 days; (P18) = storage for 18 days and (P24) strage for 24 days. Each treatment was repeated 4 times. Observed variables are pH, water holding capacity, and cooking shrinkage data were analyzed with analysis of variance and when a treatment effect followed by Duncan's Multiple range test. Data of organoleptic was analyzed by Kruskal Wallis test. Conclusions from the results obtained by analysis and discussion of that storage time was significantly effect on pH, cooking loss, flavour, color and texture of broiler chicken meat, but no to water-holding capacity. The time lenght storage of broiler chicke meat, could reduced pH and cooking loss, flavor, texture and color but water-holding capacity was increased. Broiler chicken meat on plastic packaged stored in the refrigerator for 6 days the quality is still good.